Witnesses of coherence and dimension from multiphoton indistinguishability tests - Taira Giordani; Chiara Esposito; Francesco Hoch; Gonzalo Carvacho; Daniel J. Brod; Ernesto F. Galvão; Nicolò Spagnolo; Fabio Sciarrino (Physical Review Research, 2021)
Quantum coherence marks a deviation from classical physics, and has been studied as a resource for metrology and quantum computation. Finding reliable and effective methods for assessing its presence is then highly desirable. Coherence witnesses rely on measuring observables whose outcomes can guarantee that a state is not diagonal in a known reference basis. Here, we experimentally measure a type of coherence witness that uses pairwise state comparisons to identify superpositions in a basis-independent way. Our experiment uses a single interferometric setup to simultaneously measure the three pairwise overlaps among three single-photon states via Hong-Ou-Mandel tests. Aside from coherence witnesses, we show the measurements also serve as a Hilbert-space dimension witness. Our results attest to the effectiveness of pooling many two-state comparison tests to ascertain various relational properties of a set of quantum states.